2003
DOI: 10.1097/01.tp.0000089242.86443.40
|View full text |Cite
|
Sign up to set email alerts
|

Roles of tumor necrosis factor-related apoptosis-inducing ligand in corneal transplantation

Abstract: TRAIL appears to play an important role in corneal-allograft rejection and may be used to prolong the survival of allografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…A recent report suggested that the attenuated rejection of corneal allografts that overexpressed TRAIL was caused by its apoptosis-inducing action on inflammatory cells (38). Probably, a beneficial action of TRAIL on xenograft survival can only be evaluated in vivo.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent report suggested that the attenuated rejection of corneal allografts that overexpressed TRAIL was caused by its apoptosis-inducing action on inflammatory cells (38). Probably, a beneficial action of TRAIL on xenograft survival can only be evaluated in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…TRAIL might be able to inhibit graft rejection of a TRAIL-expressing xenograft, although T cells are not dispatched. Recently, TRAIL was reported to inhibit the primarily T-cell-mediated rejection of corneal allografts (38). Thus, expression of human TRAIL in transgenic pigs may provide a reasonable strategy for protecting pig tissues against cell-mediated rejection after xenotransplantation to primates.…”
mentioning
confidence: 99%
“…TRAIL has been implicated in apoptosis of activated T cells and has been found to promote the proliferation of Tregs (28). Although no studies have directly associated TRAIL expression with corneal graft survival, transfection of mouse donor corneas with adenovirus carrying TRAIL gene has been shown to significantly improve corneal allograft survival (29). In addition to these membrane-bound proteins, several soluble immunoregulatory factors are found in the aqueous humor of the eye including TGF-β 2 , complement regulatory proteins (CRP), alpha-melanocyte stimulating hormone (α-MSH), vasoactive intestinal peptide (VIP), calcitonin gene-related peptide (CGRP), somatostatin, macrophage migration inhibitory factor (MIF) and indoleamine 2, 3-dioxygenase (IDO), which are involved in tolerance induction in macrophages, regulation of dendritic cells, and inhibition of complement and NK cell-mediated cell lysis and T cell activation (3039).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover TRAIL acts as a cell cycle inhibitor for T-cells independent of their differentiation status or antigen specificity (Song et al, 2000;Lunemann et al, 2002). Recently TRAIL was reported to inhibit the primarily T-cell mediated rejection of corneal allografts (Xie et al, 2003). Thus, expression of human TRAIL in transgenic pigs might be a strategy to protect pig tissues against cell-mediated rejection after xenotransplantation to primates (Klose et al, 2005).…”
Section: Copyright © 2005 S Karger Ag Baselmentioning
confidence: 99%